Not quite a cure yet: unlocking the unfulfilled promise of live biotherapeutics for disease treatment - Verdugo-Meza, Andrea; Chiang, Han M.; Mayer, Emeran A.; Gibson, Deanna L. (Frontiers in Pharmacology, 2025)
Few live microbial therapeutics have demonstrated conclusive or reproducible clinical efficacy. Cochrane meta-analyses of probiotic interventions across multiple clinical trials, analyzed using a rank-biserial correlation test, revealed that intestinal inflammation is negatively correlated with clinical responsiveness. This is exemplified by Escherichia coli Nissle 1917, which shows efficacy in maintaining remission comparable to frontline therapies, yet fails to demonstrate clear benefit in the treatment of active ulcerative colitis, an inflammatory bowel disease defined by chronic intestinal inflammation. Beyond inflammation as a key barrier to efficacy, inadequate shelf life and delivery strategies further compromise microbial viability and functional persistence in the gastrointestinal tract. Here, we highlight both the challenges and emerging opportunities in the field of live microbial therapeutics, emphasizing the urgent need to integrate scientific, clinical, and industrial efforts to achieve durable and clinically meaningful outcomes.